PENGEMBANGAN MEDIA KOMIK KERAGAMAN BUDAYA BERBASIS CANVA UNTUK MENINGKATKAN KREATIVITAS DAN SIKAP NASIONALISME SISWA SD - Prahastiwi, Linda; Qisti Barriyah, Insanul; Wibawa, Sutrisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce Canva-based cultural diversity comic media, determine the feasibility and effectiveness of Canva-based cultural diversity comic media in increasing creativity and nationalistic attitudes in fourth grade elementary school students. Development research was carried out using the ADDIE model (Analysis, Design, Develop, Implement, Evaluate). Based on the results of research and development, it shows that (1) learning comic media is suitable for use in learning. According to material experts and learning media experts, comic media products are in the "good" category. (2) there is an increase in creativity and nationalistic attitudes between the control class and the experimental class. All tests and research results show that learning comic media has a positive and significant effect on students' motivation to learn Indonesian and students' reading comprehension skills. Eligibility is obtained after being tested by media validators and practical validators. The results of the media feasibility test showed a good percentage (88.7%) in terms of material, a good percentage (86.4%) in terms of cultural diversity comic media, a good percentage (85.8%) in terms of learning design. Limited trials were also carried out by researchers, the percentage results were very good (92.5%). Meanwhile, the small group trial had a good percentage (85.7).